Alternative sources use and misinformation exposure and susceptibility: The curvilinear moderation effects of socioeconomic status. (May 2022) - Wang, Tianjiao; Yu, Wenting
Highlights: This study responds to a call for rediscovering the role of socioeconomic status (SES) in studies of misinformation exposure and susceptibility. Poisson regression models were fitted with the data coming from an online survey with 955 Chinese respondents. Alternative sources use in mainland China is found to be positively related to misinformation exposure and susceptibility, respectively. Socioeconomic status (SES), indicated by income levels, is found to quadratically moderate the relationship between alternative sources use and misinformation exposure/susceptibility. In contrast, educational attainment, another usual indicator of SES, does not show support for a quadratic moderation effect hypothesis. Abstract: In an era of post-truth, the rise of alternative information sources is often blamed for the spread of misinformation. This study responds to a call for rediscovering the role of socioeconomic status (SES) by investigating the quadratic moderation effects of SES on associations between the use of alternative sources and misinformation exposure and susceptibility. Poisson regression models were fitted with the data coming from an online survey with 955 Chinese respondents. Findings show that the moderation effects are quadratic when income, rather than educational attainment, serves as the measurement of SES. The implications of the findings with respect to overeducation, income's cognitive effects, and the non-equivalence of SES's common measures in studies of media effects are discussed.